The expansion of export potential of Kyrgyzstan with the countries of the Great silk road (Journal of Economic Research & Business Administration, 2016)
The article indicates the importance of the Great Silk Road (GSR) and also those branches, which play an important role for the development of foreign policy of Kyrgyzstan, in particular, export sides were highlighted. In this regard, the dynamics of exports and imports of Kyrgyzstan for some years, the structure of its trade with the countries of GSR were analyzed and nowadays basic obstacles on the development of an export policy were pointed.The authors substantiated the needs for tourism services export, which is one of the most perspective and profitable sectors of the country. In addition, the main economic indicators presented in the article also proved it. The article presents the views of tourism resources as natural, recreational, historical and cultural which are the most effective tools for tourist attraction.The development of infrastructure, primarily a business hotel, tourist centers serving the tourism industry and the problems hindering its development were marked by the authors in the article. The authors have high hopes that Kyrgyzstan will be a great world tourist destination in the future.
Keywords: Great Silk Road; foreign trade; international business tourism; tourism infrastructure; global tourist center.